68.7k views
2 votes
How to use distributive property to remove the parentheses

1 Answer

4 votes

Answer: Multiply the number(s) outside the parenthesis by the numbers inside the parenthesis. The distributive property is expressed in math terms as the following equation: a(b + c) = ab + ac.

Explanation:

2(3 + 4) - 12 Multiply 2 times 3 first.

2 x 3 = 6.

Then multiply 2 times 4.

2 x 4 = 8.

Remember our equation earlier? a(b + c) = ab + ac.

In this case, 2 is a, 3 is b, and 4 is c.

So 2[a](3[b]+4[c]) = 2[a](3)[b] + 2[a](4)[b].

Let's rewrite this in a way that can be read better.

2(3+4) - 12 = 2(3) + 2(4) - 12.

2(3+4) - 12 = 6 + 8 - 12.

2(3+4) - 12 = 14 - 12.

2(3+4) - 12 = 2.

Hope this helped! :)

User Rotemx
by
5.6k points